ASSOCIATION BETWEEN NUTRITIONAL PROFILE AND MULTIMORBIDITY IN PATIENTS WITH MORBID OBESITY (CIPEEX, 2025)
Severe obesity is strongly associated with a higher prevalence of chronic diseases and health complications, leading to increased rates of multimorbidity. Nutritional status plays a key role in the development and progression of these conditions; however, evidence linking nutritional profile and multimorbidity in severely obese populations is still scarce. This ongoing observational study aims to investigate the association between nutritional profile and multimorbidity in adults with severe obesity. A cross-sectional design will be conducted with patients recruited from the public healthcare system, based on referrals provided by the State Health Department. Data collection will include sociodemographic characteristics, clinical history, anthropometric measures, dietary intake, and biochemical parameters. Multimorbidity will be defined as the presence of two or more chronic conditions, and its association with nutritional indicators will be analyzed using descriptive statistics and multivariate regression models. As data collection is in progress, preliminary findings are expected to provide insights into nutritional risk factors related to multimorbidity in this population. The results will contribute to improving clinical management and guiding public health strategies targeting individuals with morbid obesity.